Kualitas Pelayanan Terhadap Kepuasan Penerima Layanan Di Dinas Kependudukan Dan Pencatatan Sipil Kabupaten Agam - Monica Seles; Armiati Armiati (Jurnal Ecogen, 2021)
The purpose of this research is to determine the effect of service quality on the satisfaction of service recipients in the population and civil registration services of religious districts. The quality of this service is measured using five dimensions, namely tangibles, reliability, responsiveness, assurance, and empathy. The research sample was 100 service recipients using the Wibisono formula taken using accidental sampling technique. The data collection technique is by using a questionnaire. The research instrument test used validity and reliability tests. At the data analysis stage, descriptive analysis and inductive analysis were carried out. Inductive analysis, namely normality test, multicollinearity test, heteroscedasticity test, and multiple regression analysis. Hypothesis testing used the F test, t test, and test the coefficient of determination (R2). The results showed that the five variables of service quality simultaneously affect the satisfaction of service recipients, and the msost influential variable is assurance.Keywords : tangibles, reliability, responsiveness, assurance, empathy, and service recipient satisfaction